Turkish community pharmacists' self-report of their pharmacies' physical atmosphere - Simge Cagirci; Selen Yegenoglu; Mehmet Mithat Uner (Wolters Kluwer Medknow Publications, 2012)
Objective: There is a great recognition that store interiors and exteriors can be designed to create feelings in potential customers which can have an important reinforcing effect on purchase. In this study it is mainly aimed to explore the behaviors of the community pharmacists related to their store's physical environment. Also we aimed to determine whether any difference exist between behaviors of pharmacists serving in high and low socio-economic regions. Methods: A total of 200 pharmacists that work socio-economically different regions were randomly selected from 1424 pharmacists registered in Ankara Chamber of Pharmacists. A uniform questionnaire was applied to the pharmacists by using a face-to-face interview technique. Findings: There are differences in terms of behavior between the pharmacists serving in high and low socio-economic regions within the context of putting importance to their stores' atmosphere. More pharmacists attach importance to the physical sight of their pharmacy serving in high socio-economic regions (90%) vs. pharmacists in low socio-economic regions (70%). Also pharmacists in high socio-economic regions indicated higher importance level of selection of the decoration equipments (84%) than pharmacists serving in high socio-economic regions (60%). Conclusion: Our study suggests that some pharmacists pay more attention to interior atmospheric elements and others do not. There is a difference in terms of attaching importance to some store atmospheric elements (i.e. physical site, decoration equipment, it's color, wall color, etc.) serving in high versus low socio-economic regions in this context.